A farewell to the MNCS and like size-independent indicators. Issue 2 (May 2016) - Abramo, Giovanni; D'Angelo, Ciriaco Andrea
Abstract: The arguments presented demonstrate that the Mean Normalized Citation Score (MNCS) and other size-independent indicators based on the ratio to publications are not indicators of research performance. The article provides examples of the distortions when rankings by MNCS are compared to those based on indicators of productivity. The authors propose recommendations for the scientometric community to switch to ranking by research efficiency, instead of MNCS and other size-independent indicators.